Distribution of various pathogenic bacteria from pediatric ward settings - Butt, Irfan A; Aslam, Bilal; Rasool, Muhammad H; Shafiq, Humerah B; Khurshid, Mohsin; Aslam, Muhammad A (Saudi medical journal, 2016)
To test various items in hospital environment as reservoirs of bacteria. Methods: This simple descriptive study was conducted between June and December 2014. Pediatric wards of 4 different hospitals of Faisalabad, Pakistan were selected and 8 different items per hospital were sampled (n=160). Poisson regression analysis was carried out with R software and using lme4 package. Results: There were no differences between the  hospitals regarding total number of bacterial isolates or bacterial isolates per sample source or prevalent bacterial species. Utensile tables were significantly the least contaminated source when comparing all sample sources from all hospitals (p=0.05). When testing if the bacterial species differed significantly between sample sources, Escherichia coli (p=0.05) and Bacillus (p=0.04) were found significantly high on utensils, while Pseudomonas was found significantly less on curtains (p=0.03) and doors (p=0.02). Conclusion: Due to unhygienic practices in hospitals children are exposed to pathogens steers to life threatening infection. A good control strategy should be implemented to avoid health care-associated infection.